Agglutination of bacteria using polyvalent nanoparticles of aggregation-induced emissive thiophthalonitrile dyes. Issue 27 (24th June 2016) - Schmidt, Bettina; Sankaran, Shrikrishnan; Stegemann, Linda; Strassert, Cristian A.; Jonkheijm, Pascal; Voskuhl, Jens
Abstract : A novel class of aggregation-induced emissive bis(phenylthio)phthalonitrile dyes were synthesized. Abstract : A novel class of aggregation-induced emissive bis(phenylthio)phthalonitrile dyes were synthesized. These dyes assembled into nanoparticles that were equipped with mannose units. The nanoparticles underwent selective interactions with lectins and bacteria. The bright fluorescent aggregates aid in the visualization of the agglutination of bacteria.